Factors Affecting 30-Day Mortality following Primary Elective Total Knee Arthroplasty: A Database Study of 326,157 Patients - Zhai, Kevin; Orr, Melissa; Grits, Daniel; Emara, Ahmed K.; Rothfusz, Christopher A.; Piuzzi, Nicolas S. (The Journal of Knee Surgery, 2021)
Despite its rarity, the risk of mortality following primary elective total knee arthroplasty (TKA) is a critical component of surgical decision-making and patient counseling. The purpose of our study was to (1) determine the overall 30-day mortality rate for unilateral primary elective TKA patients, (2) determine the 30-day mortality rates when stratified by age, comorbidities, and preoperative diagnosis, and (3) identify the distribution of (i) patient demographics, (ii) baseline comorbidities, and (iii) preoperative diagnoses between mortality and mortality-free cohorts. A total of 326,157 patients underwent primary elective TKA (2011–2018) were identified through retrospective review of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. Patients were divided into 30-day mortality (n = 320) and mortality-free (n = 325,837) cohorts. Patient demographics, preoperative comorbidities, and preoperative diagnoses were compared. Age group, American Society of Anesthesiology (ASA) score, and modified Charlson Comorbidity Index (CCI) scores were normalized per 1000 and stratified by preoperative diagnosis. The overall mortality rate was 0.098%. Older age (p < 0.001) and male gender (p < 0.001) were associated with increased mortality. There was no association between mortality and race (p = 0.346) or body mass index (BMI) class (p = 0.722). All reported comorbidities except smoking status were significantly greater in the mortality cohort (p < 0.05). For ASA scores of I, II, III, and IV, the number of deaths per 1,000 were 0.16, 0.47, 1.4, and 4.4, respectively. For CCI scores of 0, 1, 2, 3, 4, and 6, mortality rates per 1,000 were 0.76, 2.1, 7.0, 11, 29, and 7.6, respectively. Mortality rates for a preoperative diagnosis of osteoarthritis (OA) versus non-OA were, respectively, 0.096% and 0.19% (p < 0.001). Increased age, male gender, increased comorbidity burden, and non-OA preoperative diagnoses are associated with higher rates of 30-day postoperative mortality. There were no significant associations between BMI or race and 30-day mortality. These findings aid in identifying of higher-risk patients, who can then receive appropriate counseling or preoperative interventions to reduce the risk of perioperative mortality.
Keywords: mortality; elective total knee arthroplasty; complications; 30-day mortality; high-risk factors